Effect of long‐term fertilization on soil microbial activities and metabolism in Paulownia plantations. (6th August 2021) - Liu, Sen; Li, Peng; Gan, Weixiang; Fu, Yujia; Weng, Yilin; Tu, Jia; Lu, Sheng; Wu, Lichao
Abstract: Paulownia is a well‐known, fast‐growing tree genus that is widely planted for commercial cultivation in the warm temperate zone of the North China Plain. Fertilization as a standard practice can efficiently increase wood production and tree yield in those Paulownia plantations, but how different fertilization measures might affect soil microbial activity, microbial biomass and metabolic functioning unclear, especially in the subtropics. To fill this knowledge gap, we initiated long‐term different fertilization experiments from afforestation, using a completely randomized block design consisting of a control, inorganic fertilizer, microelement‐inorganic fertilizer and organic–inorganic compound fertilizer (OIF) treatments in South China's subtropical zone. The results revealed fertilization significantly increased soil enzyme activity and microbial biomass, especially that of urease, invertase, acid phosphatase, as well as the microbial biomass in terms of carbon and nitrogen, all of which increased most significantly in soil under the OIF treatment. The carbon source utilization levels of five carbon substrates under the OIF treatment, namely D‐xylose, glucose‐1‐phosphate, D‐cellobiose, α ‐ketobutyric acid and glycogen, were significantly higher than those of the others. From these data, we may reasonably infer that the application of organic fertilizer could offer an effective management practice for use in Paulownia plantations. The five carbon matrices may be the most efficient carbon sources for increasing the abundance of efficient soil microorganisms, improving soil fertility and achieving the sustainable development of Paulownia plantations.